An empirical study on the viability of Islamic banking system in Nigeria: a case study of Lagos state - Danbatta, Bello Lawal (Instiute of Islamic Banking and Finance,International Islamic University Malaysia, 2011)
The Nigerian Banking and Other Financial Institutions Decree (BOFID No.25) of 1991 has been amended to permit banking transactions based on Profit and Loss Sharing (PLS) arrangement, but yet there is no single Islamic Bank in Nigeria. All efforts by both the regulators and the bankers to establish Islamic Banking system in Nigeria have become unrealizable because of certain unclear factors. This study was conducted to critically analyze the viability of Islamic banking system in Nigeria taking Lagos State as a case study. In making the study, dimensions of viability that includes Market, Economic, Financial, Business, Political and Social viability and their components such as interest, desire, awareness, attitude, perception, preferences, acceptance, business, social and political inclinations were investigated using three sets of questionnaires that were directed to five groups of respondents namely, potential individual customers, business entities, government agencies, professionals in the banking sector and regulators of the Nigerian banking industry. The data gathered for this research were sufficient and adequate for the analyses conducted. Using descriptive statistics, parametric and other non-parametric statistical techniques, it was found that religious sentiments, wrong perceptions and poor public awareness were the key factors that hindered the establishment of Islamic Banking. Other factors such as acceptance to participate, interest to bank, competence and attitude of the regulators and services providers, and economic instability also affect the overall viability of Islamic Banking system. This study gives some implications for some issues like taxation, regulatory framework and the two approaches in establishing Islamic Banking systems; i.e. full pledge and window schemes to be adopted in Nigeria.